PENGARUH PARTISIPASI KARYAWAN, PENGEMBANGAN KARIR DAN KOMPENSASI YANG DITERIMA TERHADAP INTENTION TO STAY KARYAWAN PRODUKSI PT. PANTJATUNGGAL KNITTING MILL - Yokhebed Ernest Ratu Tyas; widiartanto widiartanto (Jurnal Ilmu Administrasi Bisnis, 2018)
Retaining employees is becoming a necessity for companies today. The participation of the employees role encourages employees to taste will have company so not difficult for employees to maintain the quality of the resulting product. Besides career development can add to the sense og belonging will be of the company. Compensation received influence on intention to stay of employees in the company. Think about employees, welfare and increase facilities will be the added value of the company. The proposed hypothesis there is the influence of employee participation, career development and compensation received against the intention to stay the production employees of PT. Pantjatunggal Knitting Mill. This type of research is explanatory research. The technique of sampling is Probaility Sampling. A type of Simple Random Sampling with the sample as much as 91 respondents as well as. The questionnaire as an instrument of research, methods of analysis used in this study using linear regression analysis with the help og 21.0 SPSS For Windows. The results showed that employee participation variables have significant effents (partial) against the intention to stay amounted to 7,4%. Career development variables have significant effects (partial) against the intention to stay amounted to 8,2%. The compensation has significant effects (partial) against the intention to stay by 10%. Employee participation, Career development and compensation received has significant effects (partial) against the intention to stay amounted to 15,2%. Based on the research results, then it is recommended that the company increase the compensation by better in facilities, besides giving more opportunities for employees to be able to develop a career and be more active in rate the participation of employees. Through this expected level of intention to stay at PT. Pantjatunggal Knitting Mill will increase.